Telemedicine in Neonatal Surgical Care: Innovations in Diagnosis, Management, and Follow-Up in Pediatrics and Perinatology - Halder, Arjama; Ganguly, Debashruti; Chakrabarty, Tarpan (Journal of Neonatal Surgery, 2025)
Regular hospital visits can be expensive, particularly in rural areas, due to travel costs. In the era of the Covid-19 Pandemic, where physical interaction becomes risky, people prefer telemedicine.Telemedicine has a transformed healthcare delivery system; it aims to meet the needs of current healthcare consumers. It significantly optimizes healthcare delivery by elevating accessibility and efficiency;it allows patients to receive care remotely. Telemedicine has transformed healthcare delivery, offering unparalleled convenience, accessibility and efficiency. Telemedicine has revolutionized the delivery of neonatal surgical care, especially in remote and resource-limited settings. The key advantages of telemedicine are that it enhances patient engagement, reduced hospitalization. It also enables doctors to monitor patient remotely, which leads to more effective healthcare delivery and cost saving.